Photocapacitor based on nanocomposite n-InSe<RbNO3> - Netyaga, V. V.; Vodop’yanov, V. N.; Ivanov, V. I.; Tkachyuk, I. G.; Kovalyuk, Z. D. (Technology and design in electronic equipment, 2018)
The n-InSe<RbNO3> nanocomposite material was obtained by the method of intercalation of the InSe layered single crystal from a melt of RbNO3 ferroelectric salt, which can be used for the production of a high-specific capacitance photoconductor. X-ray analysis of the structure, AFM-imaging of the surface and measurement of dielectric frequency characteristics of the samples were carried out. It was found that the intercalated InSe<RbNO3> samples keeps the type of monocrystalline structure, and the spectrum of X-ray diffraction pattern indicates the implantation of the intercalant in the van der Waals gaps of layered InSe single crystal with an increase in the parameters of the crystal lattice.AFM images of the surface of nanocomposite material layers show the RbNO3 islands in the form of nanosized rings. The islands' height does not exceed the width of van der Waals gap for InSe, which is ≈ 0,35 nm, and the average outside diameter of the rings is ≈ 50 nm. The ensemble of nanorings is characterized by a high surface density in (0001) plane of the crystal layers (109—1010 cm–2). Thus, the physical phenomena of self-organization of nanostructures with ionic conductivity on the surfaces of layers with a molecular type of bond are used in the making of nanocomposite material for the proposed photoconductor. This allows us to obtain arrays of nanosized 2D inclusions with ionic conductivity and with given geometrical sizes, morphology and spatial distribution in a matrix of a layered crystal.The developed photoconductor has a high specific electrical capacity, a high coefficient of overlapping of the capacity (≈ 109) in the light, has the ability to accumulate electric charge, it can be used as a low-voltage semiconductor device in optoelectronic memory systems, in photoelectric sensors, in light energy converter and in the storage of electric energy.